2013
DOI: 10.2460/javma.243.8.1179
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation and biochemical analyses of thiamine deficiency in Pacific harbor seals (Phoca vitulina) maintained at a zoological facility

Abstract: Results of analyses in this study confirmed a diagnosis of thiamine deficiency for affected seals resulting from high thiaminase activity in dietary fish, inadequate vitamin administration, and increased thiamine demand caused by pregnancy and lactation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 138 publications
0
23
0
Order By: Relevance
“…A study in seals found that pregnant and lactating seals were 2.5 times more likely to develop thiamine deficiency than other female seals [18]. Lactating and maybe pregnant female dolphins should be supplemented with more thiamine than non-breeding dolphins.…”
Section: Discussionmentioning
confidence: 99%
“…A study in seals found that pregnant and lactating seals were 2.5 times more likely to develop thiamine deficiency than other female seals [18]. Lactating and maybe pregnant female dolphins should be supplemented with more thiamine than non-breeding dolphins.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated a number of symptoms during sub‐lethal thiamine deficiency, including appetite loss or anorexia , memory and learning deficits , lethargy , immune suppression and damage to the blood–brain barrier . However, these early signs are not pathognomonic of thiamine deficiency and they may be overlooked when a well‐balanced diet is provided without considering genetic susceptibilities to this deficiency .…”
Section: Discussionmentioning
confidence: 99%
“…likely that the progression of the neurological disease that culminated in death was caused by a localized thiamine deficiency originated by the presence a loss-of-function mutation in SLC19A3.1, gene encoding for a thiamine transporter. Several studies have indicated a number of symptoms during sub-lethal thiamine deficiency, including appetite loss or anorexia (25), memory and learning deficits (62,63,92), lethargy (34), immune suppression (34) and damage to the blood-brain barrier (20,46). However, these early signs are not pathognomonic of thiamine deficiency and they may be overlooked when a wellbalanced diet is provided (25) without considering genetic susceptibilities to this deficiency (40,78).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some factors interfere significantly with thiamin absorption, such as the type of food processing, alcohol intake, protein and folate nutrition level, and the presence of antithiaminic factors in the diet . Intake of raw foods with high thiaminase content (such as crustaceans, sprouts, microorganisms, and some fish) can contribute or even be the direct cause of thiamin deficiency . Thiaminase is also thermolabile, and the act of cooking these foods considerably reduces the risk of thiamin deficiency .…”
Section: Thiamin: Function and Sourcesmentioning
confidence: 99%